Design, build and test a passive thermal system for a loft : a roof solar chimney application for South African weather conditions - Beviss-Challinor, Lauren Margaret (Stellenbosch : Stellenbosch University, 2010)
Thesis (MEng (Mechanical and Mechatronic Engineering))--Stellenbosch University, 2007.